Pengaruh Transparansi, Kompetensi, dan SPI Terhadap Akuntabilitas Pengelolaan Keuangan pada BPKAD Papua - Yustina Ribka Manggaprouw; Ratna Anggraini; Muhammad Yusuf (LPPM Universitas Negeri Jakarta, 2025)
This study attempts to ascertain the impact of transparency, competence, and internal control systems on financial management accountability at the BPKAD Papua. This research uses secondary data collected through questionnaires with financial management employees using purposive sampling techniques, thereby obtaining a population of 45 people. The data analysis of this study used multiple linear regression with an ordinary least squares (OLS) approach using SPSS 23 software. The research results show that partially transparency has a positive and significant effect on regional financial management accountability, while competence and the internal control system do not have a significant effect. then simultaneously these three independent variables have a positive and significant effect on regional financial management accountability. Due to the minimal number of research samples, further research can increase the number and variety of samples so that the results obtained are stronger and more effective